Inovasi Kurikulum Bahasa Arab di Madrasah Aliyah Pacitan: Pendekatan Multimahārah - Ahmadi Ahmadi; Biqi Asshafah Zain (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2026)
This study examines Arabic curriculum innovation at Madrasah Aliyah Pacitan through a multi-mahārah approach integrating four language skills. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the innovation of the Arabic curriculum is carried out by innovating Arabic learning tools that are directed to support the multi-mahārah approach in a structured manner in the form of preparing learning tools (teaching modules, syllabus, and lesson plans) that contain integrated skills-based learning objectives and the use of a contextual approach in delivering the material. Innovation of learning strategies and techniques to accommodate the multi-mahārah approach by implementing project-based learning, conversation simulations, group discussions, and the use of digital media. However, several challenges remain, such as limited lesson time and teacher readiness in implementing the approach optimally.